2012
DOI: 10.1021/jo301848g
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl Shifts in Substituted Arenes via Ipso Arenium Ions

Abstract: The isomerization of substituted arenes through ipso arenium ions is an important and general molecular rearrangement that leads to interconversions of constitutional isomers. We show here that the superacid trifluoromethanesulfonic acid (TfOH), ca. 1 M in dichloroethane (DCE), provides reliable catalytic reaction conditions for these rearrangements, easily applied at ambient temperature, reflux (84 °C), or in a microwave reactor for higher temperatures. Interconversion of terphenyl isomers in TfOH/DCE at 84 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 117 publications
7
39
0
2
Order By: Relevance
“…Rathore and co-workers have demonstrated that ortho-terphenyl derivatives such as 7 undergo efficient Scholl cyclizations in the presence of DDQ/MeSO 3 Ht hrough the generation of radical cations such as 7C + (Figure 4). [6f] Consistent with the reported results for 7, [6f] cyclization or aryl migration [15] was not observed for 3 in acidic media using MeSO 3 H, implying that it should be unlikely that the cyclization of 3 proceeds by the arenium ion pathway.…”
supporting
confidence: 83%
“…Rathore and co-workers have demonstrated that ortho-terphenyl derivatives such as 7 undergo efficient Scholl cyclizations in the presence of DDQ/MeSO 3 Ht hrough the generation of radical cations such as 7C + (Figure 4). [6f] Consistent with the reported results for 7, [6f] cyclization or aryl migration [15] was not observed for 3 in acidic media using MeSO 3 H, implying that it should be unlikely that the cyclization of 3 proceeds by the arenium ion pathway.…”
supporting
confidence: 83%
“…Many reports highlighted the importance of temperature and/or the presence of acid to catalyze the process [18][19][20][21][22]. In present case, the pyridine-2-carboxaldehyde (99 %) contains 0.5 % of the free acid and it is possibly the source of H + that catalyze the isomerization of the methyl group (steps 1, 2 and 3 in Scheme-II).…”
Section: Resultsmentioning
confidence: 86%
“…Isomerization of alkyl and aryl groups in arene rings has been reported in literatures [18][19][20][21] and such reaction has been used in many industrial processes including the conversion of mixed xylene to p-xylene [22]. Many reports highlighted the importance of temperature and/or the presence of acid to catalyze the process [18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Details of these systems can be found in [1,3,4,8,10,13,14,16,17]. In what follows, we simply refer to them as A, B, C, D, E, and F. Similarly, our discussion in Section 3 implies that ( ) ( ).…”
Section: Comparison With Physical Propertiesmentioning
confidence: 99%